The role of eNOS gene polymorphisms in immunopathogenesis of primary open-angle glaucoma - O. A. Svitich; A. R. Kinkulkina; H. S. Avagyan; T. V. Gavrilova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2022)
Introduction. Pathologies of the visual organ (keratitis, glaucoma, etc.) occupy a leading place among the causes of vision loss and blindness. According to the literature, the immunopathogenesis of bacterial keratitis is associated with the activation of macrophages and oxygen explosion. The role of these mechanisms in the pathogenesis of primary open-angle glaucoma is not fully understood. There are isolated studies in which the development of this pathology is associated with nitric oxide NO, which is produced by endothelial NO synthase (nos). However, despite numerous studies, the role of immunogenetics in the pathogenesis of glaucoma remains insufficiently researched.